2015
DOI: 10.2169/internalmedicine.54.3620
|View full text |Cite
|
Sign up to set email alerts
|

A Rare but Potentially Lethal Case of Tuberculous Aortic Aneurysm Presenting with Repeated Attacks of Abdominal Pain

Abstract: Tuberculous aortic aneurysm is an extremely rare disease with a high mortality rate. The clinical features of this condition are highly variable, ranging from asymptomatic with or without constitutional symptoms, abdominal pain to frank rupture, bleeding and shock. We herein report the case of a 56-year-old man with a large tuberculous mycotic aneurysm in the abdominal aorta with an initial presentation of repeated attacks of abdominal pain lasting for several months. Due to the vague nature of the initial sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%
“…It kills millions of people worldwide each year and is the second leading cause of death from infection. The World Health Organization (WHO) reported 8 million new cases and about 1.3 million people died of the disease in 2012 [1] . TB can have a variety of clinical manifestations due to its spread to organs other than the lungs.…”
Section: Introductionmentioning
confidence: 99%